2014
DOI: 10.1177/0266242613519807
|View full text |Cite
|
Sign up to set email alerts
|

Contextualization and the advancement of entrepreneurship research

Abstract: We are indebted to Shaker Zahra, Mike Wright and Sondos Abdelgawad for their contribution to our 'Future Directions' occasional series of research papers. The focus on context is timely and apposite; in essence all social phenomena are undertaken in specific contexts which intersect to generate, enable or constrain particular forms of behaviour. Yet so often in contemporary research, the critical and dynamic influence of context is taken for granted and remains invisible and unacknowledged. Within this paper, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
495
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 533 publications
(519 citation statements)
references
References 100 publications
13
495
0
11
Order By: Relevance
“…The selection of these topics serves to remind us about the potential of qualitative research for examining the 'microfoundations' (Gagné et al, 2014;Zahra et al, 2014) of family business structures and behaviors and for 'narrowing the micromacro gap' (Bamberger, 2008, p.840) in family business research. In addition, we argue that greater scrutiny about the foundational questions we are trying to address through qualitative inquiry is important because there is no 'single, monolithic approach to qualitative research and evaluation' (Patton, 2002, p.76) or accepted 'boilerplate' that standardizes the approach to and writing of qualitative research (Pratt, 2009, p.856).…”
Section: Planning For New Futuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The selection of these topics serves to remind us about the potential of qualitative research for examining the 'microfoundations' (Gagné et al, 2014;Zahra et al, 2014) of family business structures and behaviors and for 'narrowing the micromacro gap' (Bamberger, 2008, p.840) in family business research. In addition, we argue that greater scrutiny about the foundational questions we are trying to address through qualitative inquiry is important because there is no 'single, monolithic approach to qualitative research and evaluation' (Patton, 2002, p.76) or accepted 'boilerplate' that standardizes the approach to and writing of qualitative research (Pratt, 2009, p.856).…”
Section: Planning For New Futuresmentioning
confidence: 99%
“…Being explicit about the foundational questions underlying our research choices helps a reconnection to the fundamental meanings and purpose of qualitative research. Such scrutiny would also enable examination of the 'micro-foundations' (Gagné, Sharma, & De Massis, 2014;Zahra, Wright, & Abdelgawad, 2014) of family Table 1 Key features of qualitative research and distinctive traits in the family business field.…”
Section: Introductionmentioning
confidence: 99%
“…Using HLMs, this study better incorporates within-and between-region /industry characteristics and overcomes the violation of independence of error terms (Zouaghi, Hirsch and Garcia, 2016;Short et al, 2009). As entrepreneurship research on the context of entrepreneurs and small businesses' activities emerges, on the other hand, it is not sufficient to simply control for contextual variables in the analysis of entrepreneurial innovations (Zahra, Wright and Abdelgawad, 2014). As Aldrich and Martinez (2001) noted, it might grossly ignore the micro foundations of entrepreneurial activities.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Autio et al (2014) provided a list of contexts that are important for entrepreneurial innovation: temporal; spatial; organizational; institutional/policy; social; and industry/technology. Further, Zahra, Wright and Abdelgawad (2014) argued that because contextual factors can explain entrepreneurial activities with particular meaning, they should not be used just as controlling variables in the relevant studies. 5 As National Research Council (2014, p. 240) noted, there is no simple definition of "technology transition" particularly relative to "technology commercialization."…”
Section: Objectivementioning
confidence: 99%
“…As asserted by Bamiatzi and Kirchmaier (2014), the relationship between firm strategy and growth can be properly identified only in context. According to Zahra et al (2014), contextualization is currently considered to be one of the leading forces of advancement in the entrepreneurship field. Previous research has shown that firms' strategies are dependent on the environment, especially with regard to different resources and business opportunities that can be explored and exploited (Rosenbusch et al, 2013).…”
Section: Environmental Conditions In Developed and Emerging Marketsmentioning
confidence: 99%